Hormone Fluctuation and Gene Expression During Early Stages of the Hickory Grafting Process - Qiaoyu Huang; Haixia Liu; Qinyuan Shen; Huwei Yuan; Fuqiang Cui; Daoliang Yan; Wona Ding; Xiaofei Wang; Bingsong Zheng (Plants, 2025)
Grafting involves complex hormonal interactions at graft interfaces that are not yet fully understood. In this study, we analyzed hormone fluctuations and gene expression during callus proliferation and vascular tissue differentiation in hickory (Carya cathayensis Sarg.) grafts. Cytokinin and ethylene precursor ACC levels steadily increased after grafting. The biosynthetic genes for these hormones (IPT3, ACS1, ACO1, and ACO5) exhibited heightened expression. Genes related to cytokinin signaling (RR3, ARR4, and ZFP5) and ethylene signaling (MKK9, ESE1, and ESE3) were similarly upregulated. Conversely, genes associated with jasmonic acid, abscisic acid, and strigolactone pathways were downregulated, including synthesis genes (AOC4 and AOS) and those involved in signal transduction (NAC3, WRKY51, and SMAX1). Correspondingly, JA-Ile and 5-deoxystrigol levels significantly decreased. Indole-3-acetic acid (IAA) levels also dropped during the early stages of graft union formation. These results suggest that low auxin concentrations may be essential in the initial stages after grafting to encourage callus proliferation, followed by an increase at later stages to facilitate vascular bundle differentiation. These findings imply that maintaining a balance between low auxin levels and elevated cytokinin and ethylene levels may be critical to support cell division and callus formation during the initial proliferation phase. Later, during the vascular differentiation phase, a gradual rise in auxin levels, accompanied by elevated ethylene, may facilitate the differentiation of vascular bundles in hickory grafts.